2012
DOI: 10.1063/1.4737258
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of 1/f noise in Ni/n-GaN Schottky barrier diode

Abstract: 1/f noise measurements were performed on Ni/n-GaN Schottky barrier diode under forward bias over a wide temperature range from 80 to 300 K. The noise spectra exhibited frequency dependence proportional to 1/f 0 with c varying between 0.8 and 1.1 down to 1 Hz. The spectral power density of current fluctuations, S I , was found to decrease with increase in temperature. Current-voltage (I-V) characteristics of the diodes have been measured, and metal-semiconductor interface was found to be spatially inhomogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…18 GaN based SBDs with barrier heights around 1.0 eV using different metals, like Pt, Pd, Ni, etc., have been already demonstrated. [23][24][25][26][27] As thermal stability of metal contacts is important for device operations at high temperatures and in harsh environments, several authors studied the effect of high temperature furnace annealing on Schottky barrier parameters in GaN based devices. [28][29][30][31] In most of these reports, furnace annealing is done for a relatively longer period (5-60 min) where Schottky barriers are found to degrade with increase in annealing temperature.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…18 GaN based SBDs with barrier heights around 1.0 eV using different metals, like Pt, Pd, Ni, etc., have been already demonstrated. [23][24][25][26][27] As thermal stability of metal contacts is important for device operations at high temperatures and in harsh environments, several authors studied the effect of high temperature furnace annealing on Schottky barrier parameters in GaN based devices. [28][29][30][31] In most of these reports, furnace annealing is done for a relatively longer period (5-60 min) where Schottky barriers are found to degrade with increase in annealing temperature.…”
mentioning
confidence: 99%
“…Prior to Ohmic metallization, samples are ultrasonically cleaned using standard procedure. 25 metal mask. RTA of the Ohmic contacts is performed in N 2 ambient at 750 C for 30 s to improve the Ohmic contact quality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…19 In addition to this, IF of 1.04 and higher SBH of 1.15 eV were calculated from I-V measurements for Cu/n-GaN, as compared to the values for Ni/n-GaN where IF and SBH were found to be 1.05 and 0.97 eV, respectively. From the previous reports on Ni/n-GaN Schottky barrier diodes, [13][14][15][16] it has been observed that in this metal/semiconductor diode, the SBH lied in between the values predicted by the Schottky-Mott model 20,21 (φ B = φ m − χ) and the Bardeen model 22 (φ B = (E g /q) − φ o ). Here, φ B is the SBH, φ m is the metal work function, χ is the electron affinity of the semiconductor, E g is the bandgap of the semiconductor, q is the electronic charge and φ o is the energy location of the charge neutrality level.…”
Section: Introductionmentioning
confidence: 99%